Geochemical implications for gas hydrate occurrence and seepage at Sites GMGS5-W07 and W09 in Qiongdongnan Basin, South China Sea - Lu, Yinghan; Yang, Hailin; Lu, Hailong; Fang, Yunxin; Kuang, Zenggui (Frontiers in Earth Science, 2022)
The compositions and morphological characteristics of minerals and the cycle of trace elements in sedimentary environments are considered to be powerful indicators for the occurrence and evolution of gas hydrates. In this article, total organic carbon (TOC) content, particle size distribution, mineral composition, element distribution, and iron speciation of sediments from sites GMGS5-W07 and GMGS5-W09 of the South China Sea are studied. The high content of TOC and the occurrence of authigenic mineral assemblages suggest the accumulation potential of gas hydrate at the two sites. In the methane-rich layers, redox-sensitive trace elements, such as Co, Ni, Cu, Zn, As, Sb, Fe, and Mn, are enriched while reducing conditions lead to the accumulation of Fe and the increase of Fe(II) species proportion in sediments. Enrichment factors and Pearson correlation analysis of trace elements show that the circulation of trace elements at site W07 is more strongly affected by methane-rich fluids than at site W09. Fe-oxyhydroxides play a critical role in the development of As and Sb enrichments, and in particular, seep fluids may be a pivotal extra input of Mo, As, and Sb at site W07. Therefore, more intense methane seepage might have happened at site W07, and this conjecture has been further confirmed by higher Sr/Ca in sediments. Based on these results, the change in seepage intensity is not associated with the occurrence of gas hydrate.